2019
DOI: 10.1007/s42235-019-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Laser Ablation and Chemical Modification for Fast Fabrication of Bio-inspired Super-hydrophobic Surface with Excellent Self-cleaning, Stability and Corrosion Resistance

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Chen et al [ 11 ] produced a reed-leaf-like (superhydrophobic stainless surface with the WCA of 157 ± 1° and WRA of 1.0 ± 0.5° by using nanosecond laser irradiation, and it exhibited good corrosion resistance. Yang et al [ 12 ] found that the laser-fabricated aluminum superhydrophobic surface with the WCA of 160.6 ± 1.5° and WRA of 3 ± 1° exhibited perfect self-cleaning capability, long-term stability, and excellent chemical stability in acidic as well as alkaline solutions. Fadeeva et al [ 13 ] reported that the laser-produced superhydrophobic Ti surface with the WCA of 166 ± 4° exhibited good antibacterial property.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 11 ] produced a reed-leaf-like (superhydrophobic stainless surface with the WCA of 157 ± 1° and WRA of 1.0 ± 0.5° by using nanosecond laser irradiation, and it exhibited good corrosion resistance. Yang et al [ 12 ] found that the laser-fabricated aluminum superhydrophobic surface with the WCA of 160.6 ± 1.5° and WRA of 3 ± 1° exhibited perfect self-cleaning capability, long-term stability, and excellent chemical stability in acidic as well as alkaline solutions. Fadeeva et al [ 13 ] reported that the laser-produced superhydrophobic Ti surface with the WCA of 166 ± 4° exhibited good antibacterial property.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by natural lotus leaves [ 2 ], rose petals [ 3 ], and butterfly wings [ 4 ], super-hydrophobic surfaces (i.e., apparent contact angle above 150° and sliding angle below 10°) have been successfully mimicked through the synergetic effects of micro/nanostructure fabrication and surface chemical modification [ 5 , 6 , 7 , 8 , 9 , 10 ]. Due to their enormous potential applications including anti-icing [ 11 ], drag reduction [ 12 ], self-cleaning [ 13 ], anti-bacteria [ 14 ], and corrosion resistance [ 15 ], super-hydrophobic surface mimicry has been extensively developed by state-of-the-art techniques, such as thermal imprinting [ 16 , 17 ], chemical vapor deposition [ 18 ], coating [ 19 ], electrochemical deposition [ 20 , 21 ], and laser texturing [ 22 , 23 , 24 , 25 , 26 , 27 ]. Particularly, laser texturing can be seen as one of the facile approaches, and therefore can be extensively utilized to fabricate super-hydrophobic substrates owing to its precise control of surface fabrication with three dimensional (3D) hierarchical structures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the C-Si bond was also detected locating at the 283.9 eV [39]. The detected fluoride functional groups were definitely originated from the FAS molecules, resulting in the formation of super-hydrophobicity for the laser-induced surface due to the dramatic reduction of surface free energy [40].…”
Section: Surface Morphology and Chemical Compositionsmentioning
confidence: 92%